PERSEPSI MAHASISWA TERHADAP LAYANAN DIGITAL BEBAS PUSTAKA UNGGAH MANDIRI PADA WISUDAWAN PERIODE 105 DI UPT PERPUSTAKAAN UNIVERSITAS BENGKULU - Fitriani, Susialia (Jurnal Perpustakaan dan Informasi, 2024)
ABSTRACT Libraries as information resource providers are considered successful in meeting the needs and expectations of users by providing easy access both physically and digitally, and enabling users to find the resources they need. One of the library's initiatives to meet the information needs of users is the free library service in the library. A good service is one that can provide a sense of satisfaction and pleasure for the users. The self-upload library service at UPT Perpustakaan Universitas Bengkulu is one example of how online library services support government and university policies to facilitate the information transaction process and reduce the buildup of diverse user requests with limited resources. From the results of research on student perceptions of self-uploading free digital library services, a positive statement can be seen from the average respondent's answer which states that the digital service is very good in meeting the needs of library users, expressed by 59% of the questionnaire survey results with a frequency of 845 who chose the highest score of 4 (Very Good). Respondents feel happy with the existence of this service, which can help and meet user needs when using free digital library services. Keywords: Library-free, Self upload, Library services, Servqual